PSV-2 Comparison of carcass characteristics between cull Holstein and Jersey cows. (7th December 2018) - Jones, T; Francis, F; Herrick, R; McEvers, T; Lawrence, T
Abstract: The objective of this study was to compare post-mortem characteristics of Holstein (HOL; n=734) and Jersey cull cows (JER; n=1, 234). Cull cows were evaluated after immobilization/exsanguination for dairy body condition score, hock score, tongue and head condemnations, permanent incisor count, liver abnormalities, lung abnormalities, viscera condemnation, hot carcass weight, 12 th rib subcutaneous fat depth, longissimus muscle area, calculated yield grade, marbling score, lean maturity, skeletal maturity, and quality grade. Interval scale variables were non-normal and did not become normal with log, square or square root transformations. Thus, each interval scale variable was analyzed using both mixed and non-parametric models and the most conservative P -value was used. Ordinal and nominal data were analyzed using Mann-Whitney U and Chi-square tests respectively. No difference ( P ≥ 0.13) was observed for rates of tongue (6.73%), head (5.43%), or viscera (20.81%) condemnations between dairy breeds. Liver (55.06% vs 45.09%) and lung (82.12% vs 71.34%) abnormalities occurred at a greater ( P ≤ 0.04) frequency in HOL than JER, respectively. Holstein cows tended to have a greater ( P = 0.08) body condition score (3 or higher; 21.4% vs 7.6%), more ( P = 0.09) 12 th rib subcutaneous fat (0.27 vs 0.21 cm), and numerically larger ( P = 0.09) yield grades (2.27 vs 2.21) than JER. Holstein cows exhibited more ( P ≤ 0.04) permanent incisors (7.1 vs 5.6), larger longissimus muscle area (47.0 vs 44.1 cm 2 ), heavier hot carcass weights (285.2 vs 193.7 kg), and more advanced skeletal maturity (D 74 vs D 33 ) than JER. Jersey cows exhibited darker ( P < 0.01) lean color than HOL. Holstein cows had a greater ( P < 0.01; 73% vs 60%) frequency of ideal hocks than JER. Final quality grades differed ( P ≤ 0.02; USDA Standard or better 30.38% JER vs 23.15% HOL) because JER cow carcasses were younger than HOL.